Amniotic membrane transplantation (AMT) without the use of sutures/fibrin glue - Agrawal, Ajai; Pratap, V B (Nepalese Journal of Ophthalmology, 2016)
Introduction: Amniotic membrane transplantation (AMT) has been used for a wide variety of ocular surface problems. Current techniques for the AMT involve suturing of the graft or patch over the ocular surface or use of fibrin glue.Objective: To describe a new sutureless technique of amniotic membrane transplantation (AMT) without the use of sutures/fibrin glue.Materials and methods: Amniotic membrane transplantation as overlay or patch was done in fourteen eyes of eight patients with severe dry eye due to Stevens Johnson syndrome for ocular surface reconstruction, promotion of epithelization, reduction of inflammation and symptomatic relief from dry eye. In this new technique of amniotic membrane transplantation, we mount the amniotic membrane with its epithelial side up on a conformer & place it on the ocular surface without applying any sutures.Conclusion: In all the fourteen eyes of eight patients operated at our centre, the amniotic membrane take up was satisfactory, with significant reduction of inflammation and symptomatic relief from dry eye. This is a simple, fast effective technique with surgical outcomes comparable to amniotic membrane transplantation using sutures/ fibrin glue.